The type material of Gryllotalpidae Leach, 1815 (Insecta: Orthoptera: Ensifera) deposited in the Orthoptera collection of the Academy of Natural Sciences of Drexel University, Philadelphia (ANSP): an updated checklist - Silva, Daniela Santos Martins; Pereira, Marcelo Ribeiro; Sperber, Carlos Frankl (Zootaxa, 2017)
The Academy of Natural Sciences of Drexel University (ANSP) is one of the most important collections of Orthoptera in the world, housing specimens from several continents. The family Gryllotalpidae comprises about 125 valid species of which types of 10 species belonging to 5 genera are housed in this collection.